2013
DOI: 10.1111/jsm.12186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a First Treatment with Phosphodiesterase Inhibitors on Men and Partners’ Quality of Sexual Life: Results of a Prospective Study in Primary Care

Abstract: Introduction Phosphodiesterase type 5 inhibitors (PDE5is) as oral treatment for erectile dysfunction (ED) facilitate the management of ED in primary care. Still, compliance is low and general practitioners (GPs) do not always feel confident with this pathology. Aim The aim of this paper is to evaluate the impact of a first treatment with PDE5i on the patient and his partner and the management of ED by GPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
1
5
0
2
Order By: Relevance
“…Other reports showed correlations between the EHS and other parameters such as the IIEF and successful sexual intercourse [17]. The EHS was again found to be an easy and useful tool for the functional assessment of ED [18][19][20]. In the current study, multivariate analysis showed that the EHS was the only objective predictor of normal erectile function.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Other reports showed correlations between the EHS and other parameters such as the IIEF and successful sexual intercourse [17]. The EHS was again found to be an easy and useful tool for the functional assessment of ED [18][19][20]. In the current study, multivariate analysis showed that the EHS was the only objective predictor of normal erectile function.…”
Section: Discussionsupporting
confidence: 64%
“…Other reports showed correlations between the EHS and other parameters such as the IIEF and successful sexual intercourse [17]. The EHS was again found to be an easy and useful tool for the functional assessment of ED [18–20].…”
Section: Discussionmentioning
confidence: 71%
“…Regardless of which of the PDE5Is are chosen, significant improvements can be found to both the patient’s and partner’s sexual lives. 17 Both Self-Esteem and Relationship and International Index of Erectile Function scores can improve for patients who start PDE5I for the first time. The Self-Esteem and Relationship subdomains for self-esteem, overall relationship, and sexual relationship improve significantly with initial therapy for the patient.…”
Section: Evaluation Of Patient Satisfaction With Erectile Dysfunctionmentioning
confidence: 98%
“…Currently there are efforts to understand the prevalence and variables associated with ed among young adult men, due to its profound effects on fundamental aspects of the identity of this population group (feelings about masculinity, confidence, self-esteem), mental health and satisfaction sexual. 9 Therefore, the objective of this research was to evaluate the degree of ed in young adults from a primary care medical unit in Tijuana, Mexico.…”
Section: Introductionmentioning
confidence: 99%